Efficient access to chiral benzo[c]chromenes via asymmetric transfer hydrogenation of ketals. Issue 8 (8th March 2018) - Li, Yangshan; Wan, Miao; Sun, Shutao; Fu, Zhongjun; Huang, Haofei; Liu, Lei
Abstract : A highly enantioselective method to chiral α-substituted 6 H -benzo[ c ]chromenes through chiral imidodiphosphoric acid-catalyzed asymmetric transfer hydrogenation of ketals has been established. Abstract : A highly enantioselective synthetic method to access chiral α-substituted 6 H -benzo[ c ]chromenes through chiral imidodiphosphoric acid-catalyzed asymmetric transfer hydrogenation of the corresponding ketals has been established. The substituent patterns at the α-position proved to be unsusceptible to the asymmetric catalysis system, with diverse hybrid substituents including aryl and vinyl, alkynyl, and alkyl moieties that were well tolerated. In addition, the generality of the method was further demonstrated by application to 1 H -isochromene-based ketals, offering chiral α-aryl and -alkyl 1 H -isochromenes in excellent ee.